Performance of bismuth telluride modules under thermal cycling in an automotive exhaust thermoelectric generator. (15th March 2021) - Harish, S.; Sivaprahasam, D.; Jayachandran, B.; Gopalan, R.; Sundararajan, G.
Highlights: Automotive exhaust thermoelectric generator designed, built and tested up to 350 °C. Performance of bismuth telluride modules tested under cyclic thermal loading in a hot air based test rig. Cold side temperature influences the power degradation of modules. X-ray tomography identifies the thermo-physical defects formed in the modules. Abstract: Many challenges are encountered in the development of an automotive exhaust thermoelectric generator (AETEG), and its performance degradation under prolonged, fluctuating operating conditions is one of them. In this study, bismuth telluride based thermoelectric (TE) modules assembled to an AETEG were tested for their performance under cyclic heat input. Three thermal cycling profiles with the maximum heat source temperature up to 350 °C were used. The open-circuit voltage (Voc ), voltage–current (V–I) characteristics, and power output at the matched load (Pmax ) were determined at regular intervals. TE modules delivering different Voc and Pmax depending on their location on the AETEG predominantly showed marginal variations in both the parameters after testing for 150 cycles. Under prolonged testing for up to 300 cycles, a couple modules showed decreased Pmax due to their increased internal resistance (Rint ). The average specific contact resistance measured in the TE leg–electrode joints of unicouples in the degraded module indicated that cold-side joints substantially contributed to the increase in Rint . The results of microstructural and compositional analyses revealed that the increase in cold-side joint contact resistance resulted from the thermochemical degradation of the interface between TE legs–Sn-Cu solder alloy. The poor streamlined flow in some parts of the segmented cooler plate resulting in high temperature at the cold side of the module appeared to be responsible for such degradation. The present study demonstrates the importance of thermal management on the cold side for the reliable performance of modules in the AETEG system.